2015
DOI: 10.1016/j.conengprac.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Incident detection and isolation in drilling using analytical redundancy relations

Abstract: Early diagnosis of incidents that could delay or endanger a drilling operation for oil or gas is essential to limit field development costs. Warnings about downhole incidents should come early enough to allow intervention before it develops to a threat, but this is difficult, since false alarms must be avoided. This paper employs model-based diagnosis using analytical redundancy relations to obtain residuals which are affected differently by the different incidents. Residuals are found to be non-Gaussian -they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In addition, it is also observed that on the basis of considering the projection coefficient K from RKHS to Figure 3 Experimental setup for collection of testing data: (a) Front view; (b) Schematics martingale space and the global fixed confidence level a, the threshold value can be computed/adjusted adaptively according to the standard deviation computed from the past data at each step of change decision making as mentioned in Eq. (11), in other words, the threshold value is not fixed in the whole process, that is different from many existing works [7][8][9][10][11]25]. All of them are consistent with the analysis previously made in Section 3.2.…”
Section: Experiments Ii: Performance Of Adaptive Thresholdsupporting
confidence: 74%
See 3 more Smart Citations
“…In addition, it is also observed that on the basis of considering the projection coefficient K from RKHS to Figure 3 Experimental setup for collection of testing data: (a) Front view; (b) Schematics martingale space and the global fixed confidence level a, the threshold value can be computed/adjusted adaptively according to the standard deviation computed from the past data at each step of change decision making as mentioned in Eq. (11), in other words, the threshold value is not fixed in the whole process, that is different from many existing works [7][8][9][10][11]25]. All of them are consistent with the analysis previously made in Section 3.2.…”
Section: Experiments Ii: Performance Of Adaptive Thresholdsupporting
confidence: 74%
“…To address this problem, unlike existing works that directly used the original monitored variables for change detection (e.g., Refs. [6][7][8][9][10][11][12]25]), we utilize the Hilbert space embedding of distribution (HED, also called the kernel mean or mean map) to map the original data fx i g, i 2 f1; 2; . .…”
Section: Adaptive Threshold For Change Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…And they developed failure time survival model to capture heterogeneous incident variables with fixed and random specifications. Willersrud et al(2015) made a diagnosis using analytical redundancy relations to obtain residuals from the different incidents effects. Analysing data was extracted from a horizontal flow loop facilities.…”
Section: Introductionmentioning
confidence: 99%